2005
DOI: 10.1038/sj.ejhg.5201482
|View full text |Cite
|
Sign up to set email alerts
|

The place of the Basques in the European Y-chromosome diversity landscape

Abstract: There is a trend to consider the gene pool of the Basques as a 'living fossil' of the earliest modern humans that colonized Europe. To investigate this assumption, we have typed 45 binary markers and five short tandem repeat loci of the Y chromosome in a set of 168 male Basques. Results on these combined haplotypes were analyzed in the context of matching data belonging to approximately 3000 individuals from over 20 European, Near East and North African populations, which were compiled from the literature. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 31 publications
5
54
2
Order By: Relevance
“…The exception to the results of the present study is thus nicely justified in this scenario, suggesting that when a Finno‐Ugric language was introduced in Hungary, the genetic buildup of the population changed only in part, thus retaining similarities with its geographic neighbors, an example of the process called élite dominance by Renfrew (1992). On the contrary, the same case cannot be easily made for Basques (Alonso et al, 2005; Rodríguez‐Ezpeleta et al, 2010; Young et al, 2011; Martinez‐Cruz et al, 2012) or Finns, for whom, to the best of our knowledge, no available evidence suggests a similar model of partial demographic replacement associated with language replacement (Nelis et al, 2009). Thus, the comparative linguistic/genomic analysis, attempted in the present study, seems able to single out and precisely assess these differences in the population histories of the three non‐IE members of our sample.…”
Section: Discussionmentioning
confidence: 83%
“…The exception to the results of the present study is thus nicely justified in this scenario, suggesting that when a Finno‐Ugric language was introduced in Hungary, the genetic buildup of the population changed only in part, thus retaining similarities with its geographic neighbors, an example of the process called élite dominance by Renfrew (1992). On the contrary, the same case cannot be easily made for Basques (Alonso et al, 2005; Rodríguez‐Ezpeleta et al, 2010; Young et al, 2011; Martinez‐Cruz et al, 2012) or Finns, for whom, to the best of our knowledge, no available evidence suggests a similar model of partial demographic replacement associated with language replacement (Nelis et al, 2009). Thus, the comparative linguistic/genomic analysis, attempted in the present study, seems able to single out and precisely assess these differences in the population histories of the three non‐IE members of our sample.…”
Section: Discussionmentioning
confidence: 83%
“…NW African specific haplogroups were identified by further genotyping of samples that were previously described elsewhere. 5 -7,19 -21 We also included a Basque dataset 22,23 and two novel Italian samples (Lucera and Veneto; Table 1). Within these populations, all E1b1b1a chromosomes were scored for the DYS439 locus to identify the E1b1b1a-b cluster 9 and the M267 marker was investigated in those chromosomes previously identified as J*(xJ2).…”
Section: Samplesmentioning
confidence: 99%
“…14,15 The principal factors contributing to differences among Spanish populations relate to the levels of external influences, both from the Near East and North Africa. 16 It is well recognized that, with some exceptions such as the Basques, 17 the Near East influence is homogeneous in the current Spanish population. However, it has been shown that both continental and Island populations have suffered from North African influences at different levels.…”
Section: Patients and Clinical Phenotypementioning
confidence: 99%
“…However, it has been shown that both continental and Island populations have suffered from North African influences at different levels. [17][18][19][20][21] The Canary Islanders, the populations from Castilla and the southern Spanish populations from Andalusia have been reported to have the highest percentage of North African influences in Spain. 19,20 In order to meet power requirements (see Materials and methods) while preserving the homogeneity of the population, we included 179 unrelated patients, which met severe sepsis criteria, 22 from different Spanish localities with as similar as possible genetic backgrounds: Tenerife, one of the major islands of the Canarian Archipelago (a total of 64 patients) and different localities from Castilla (a total of 115 patients).…”
Section: Patients and Clinical Phenotypementioning
confidence: 99%
See 1 more Smart Citation